Consideration of the concept emotion in psychology (The Journal of Psychology and Sociology, 2015)
The article discusses the theoretical basis of psychological sciences such as emotions and feelings, and analysis of physiological nature. And also dis-cusses the development of feelings and emotions of the individual.Various difficulties and feature versatility life paths are not rare breeds of ordinary situations complicated relationship. They appear in the form of complex sensory excitement such as joy, sadness, sympathy, neglect, anger, pride, shame, and fear. Above said all the excitement related to feelings and emotions.Emotions describe a person’s need for a particular object. In the evolution of vosprtiyatie emotions affect the body and human activity. Their effect on the body is revealed through violation of factors.This way, emotion is a part that is responsible for the daily human body and the functional state of the action.However, we must use carefully these two concepts: the «feeling» and «emotions.» Ho close their meanings are? Are these concepts generated from each other?Emotions are subjective human responses to external and internal stimuli, reflecting their experience in the form of personal significance for the subject and manifest themselves in the forms of pleasure or displeasure.
Keywords: emotion; emotional condition; disorder; anxiety; affect; feel-ings.